Performance analysis of Unity 3D environment in development of a character simulation - Woźniak, Aleksandra; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2016)
This work presents the performance analysis of Unity 3D environment character simulation development. Ihe purpose of this work is a comparative analysis of character animation processes in the aforementioned environment. The analysis is based on motion simulation process, which has been shown in the two different ways. The results showed advantage of motion simulation process based on the blend tree, which was characterized by greater fluency and as it also turned out higher efficiency than the state animation.